1998
DOI: 10.1126/science.282.5394.1695
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Long-Term Decline and Recovery of an Isolated Population

Abstract: Effects of small population size and reduced genetic variation on the viability of wild animal populations remain controversial. During a 35-year study of a remnant population of greater prairie chickens, population size decreased from 2000 individuals in 1962 to fewer than 50 by 1994. Concurrently, both fitness, as measured by fertility and hatching rates of eggs, and genetic diversity declined significantly. Conservation measures initiated in 1992 with translocations of birds from large, genetically diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
483
5
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 606 publications
(497 citation statements)
references
References 17 publications
5
483
5
4
Order By: Relevance
“…Although there are quite a number of risks connected with genetic rescue (Tallmon et al 2004;Edmands 2007;Hedrick and Fredrickson 2010) including the ones discussed here, genetic rescue has proven to be a successful method to increase the fitness of genetically eroded populations and to improve their persistence (Hedrick 1995;Westemeier et al 1998;Madsen et al 1999;Willi et al 2007;Bouzat et al 2009;Hedrick and Fredrickson 2010). Thus if populations decline in numbers partly due to genetic problems and because of this have a high probability of going extinct in the near future, genetic rescue offers a viable management option, notwithstanding the risks connected to it.…”
Section: Inferences For Conservation Managementmentioning
confidence: 95%
See 1 more Smart Citation
“…Although there are quite a number of risks connected with genetic rescue (Tallmon et al 2004;Edmands 2007;Hedrick and Fredrickson 2010) including the ones discussed here, genetic rescue has proven to be a successful method to increase the fitness of genetically eroded populations and to improve their persistence (Hedrick 1995;Westemeier et al 1998;Madsen et al 1999;Willi et al 2007;Bouzat et al 2009;Hedrick and Fredrickson 2010). Thus if populations decline in numbers partly due to genetic problems and because of this have a high probability of going extinct in the near future, genetic rescue offers a viable management option, notwithstanding the risks connected to it.…”
Section: Inferences For Conservation Managementmentioning
confidence: 95%
“…frequency dependent selection for rare S-alleles in plants (Leducq et al 2010)). This concept of genetic rescue is now considered to be a realistic management option to counteract the increased extinction risk from genetic erosion (for reviews see Tallmon et al 2004;Hedrick 2005;Edmands 2007), and has been shown to be very effective in a number of cases (Hedrick 1995;Westemeier et al 1998;Madsen et al 1999;Willi et al 2007;Bouzat et al 2009;Hedrick and Fredrickson 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Population losses and the concomitant loss of genetic variation associated with these slow but sustained pressures over multiple generations have been linked to inbreeding depression and negative impacts on adaptability and fitness. Assessing the genetic effects of gradual declines is crucial to the management of shorebirds and other wildlife populations (Westemeier et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The decline in genetic diversity in populations R1-R3 as observed in this study is an important warning, as the reintroductions in these areas were performed by releasing individuals from the NL breeding line only, having already a lower genetic diversity compared with other breeding lines. Even a small decline in genetic diversity may affect population persistence of R1-R3 in the long term as a lowered genetic diversity is associated with endangered and failing populations (Madsen et al 1999;Westemeier et al 1998;Carlson et al 2014;Whiteley et al 2015), although habitat quality and habitat management often plays a more dominant role in population persistence (Spielman et al 2004;Bouzat et al 2009;La Haye et al 2014).The populations of R4-R5 were established by releasing individuals of two breeding lines (NL and G/NL). This strategy was followed to maximize levels of genetic diversity in the new populations.…”
mentioning
confidence: 99%
“…Despite these disadvantages, reintroduction has become an important and frequently applied strategy for the conservation of a broad variety of mammals, ranging from small mammals (Ottewell et al 2014;McCleery et al 2014) till large carnivores (Hayward et al 2007). Unfortunately, the overall success of reintroductions is low (Fischer and Lindenmayer 2000;Tenhumberg et al 2004;Armstrong and Seddon 2008) and several authors (Robert 2009;Weeks et al 2011) have stressed the need of giving attention to the genetic adaptive potential of reintroduced populations (Carlson et al 2014;Jamieson 2015) as a low genetic adaptive potential may hamper a successful recovery of the species (Madsen et al 1999;Westemeier et al 1998;Carlson et al 2014;Whiteley et al 2015). By implementing a systematic genetic monitoring, which we define as 'quantifying temporal changes in population genetic metrics' (following Schwartz et al 2007), when starting a reintroduction project, very important information of both the genetic status of the population and population demographic parameters can be gained, while the results of such a monitoring can be used to optimize conservation actions (Schwartz et al 2007).…”
mentioning
confidence: 99%